The Cochrane Database of Systematic Reviews 2002
DOI: 10.1002/14651858.cd001535
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic duration for treating uncomplicated, symptomatic lower urinary tract infections in elderly women

Abstract: Cochrane Database of Systematic Reviews

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 144 publications
0
46
0
4
Order By: Relevance
“…Studies have looked to find the optimal length of therapy222324 but potential treatment durations are based on empirical evidence. This study used a mathematical model as a way to determine the time to eradication of the infection and therefore the minimum duration of treatment required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have looked to find the optimal length of therapy222324 but potential treatment durations are based on empirical evidence. This study used a mathematical model as a way to determine the time to eradication of the infection and therefore the minimum duration of treatment required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three meta-analyses on general aspects of antibiotic therapy for acute uncomplicated cystitis [4][5][6] and one recently published meta-analysis on antibiotic versus placebo treatment of women with uncomplicated cystitis [7] were also considered. The studies were rated according to the level of evidence (LoE) and the grade of recommendation (GoR) using ICUD standards (for details see Preface) [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…Longer-thanneeded durations are one of the most frequent causes of unnecessary antibiotic prescriptions [14]. Several authors have shown that around half of systemic antibiotic courses in LTCFs are longer than 7 days [8,10,30], and this appeared to be influenced by prescriber preference more than patient characteristics, even though 7 days of therapy is sufficient for the most common bacterial infections encountered in LTCF residents [62][63][64].…”
Section: Target Areas Where Antibiotic Misuse Is Commonmentioning
confidence: 99%